PROTOCOLIZACIÓN DE PROCEDIMIENTOS INSTITUCIONALES, INVESTIGACIÓN EVALUATIVA Y CUMPLIMIENTO DE LOS DERECHOS DE LAS PERSONAS MENORES DE EDAD MIGRANTES NO ACOMPAÑADAS EN COSTA RICA - Chavarría Carranza, Carlos Yurán (2018)
Evaluation research is a very useful tool in those instances where organizations, internally and in their relations with others, can identify their weaknesses and strengths with which they accomplish their objectives. A situation such as the migration of unaccompanied minors made the International Organization for Migration develop an assessment of the societal response given in Costa Rica to attend to the problem. The results of this investigation show significant successes societal response is considered efficient. However, they also reveal moments where the internal and coordinated actions among institutions, weaken and even distort the fulfillment of Human Rights which should protect minors in the country.